2012
DOI: 10.1108/00400911211244704
|View full text |Cite
|
Sign up to set email alerts
|

The role of numeracy skills in graduate employability

Abstract: 8Purpose -This article explores the role and importance of numeracy skills in graduate 9 recruitment within a diversity of employment sectors. 10Design/methodology/approach -The results of a mixed-methods study, involving three 11 online surveys (including an employer survey), student focus group sessions and interviews 12 with tutors, are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 10 publications
3
39
0
1
Order By: Relevance
“…The largest gaps in the capabilities of new graduates were seen as commercial awareness, analysis and decision-making skills, communication skills, and good writing skills. In relation to numeracy skills sought by employers, research involving 165 employers indicated that the numerical tasks which employers expected graduates to be competent were calculating percentages (88%), data interpretation (85%), numerical problem solving (78%), and using spreadsheet software (78%) (Durrani and Tariq, 2012).…”
Section: Graduate Skills In Generalmentioning
confidence: 99%
“…The largest gaps in the capabilities of new graduates were seen as commercial awareness, analysis and decision-making skills, communication skills, and good writing skills. In relation to numeracy skills sought by employers, research involving 165 employers indicated that the numerical tasks which employers expected graduates to be competent were calculating percentages (88%), data interpretation (85%), numerical problem solving (78%), and using spreadsheet software (78%) (Durrani and Tariq, 2012).…”
Section: Graduate Skills In Generalmentioning
confidence: 99%
“…The importance of mathematical literacy has been noted by several authors, and it has been suggested that it may significantly affect the employability of graduates [18][19][20]. At the academic level, we found in a previous study that the average score in the subject Plant Physiology for questions that require mathematical skills for resolution are a good predictor of the students' final grades, though such issues only represent less than 15% of the questions in the examinations [7].…”
Section: Discussionmentioning
confidence: 96%
“…The exams were not time limited and 80 % of the students finished within 2 h. The adequacy of the tests to the objectives of the course was assessed by calculating the usual parameters in tests based on multiple choice questions (MCQ). The Kuder-Richardson coefficient (KR 20 ) is a measure of the internal consistency and therefore reliability of the tests and can range from 0 to 1. Values higher than 0.5 are considered sufficient for drawing meaningful conclusions [15].…”
Section: Methodsmentioning
confidence: 99%
“…Also, in working effectively in the construction industry, it is essential for graduates to possess numeracy skills (Russell et al, 2007;Pitan, 2015:31). Possessing this skill involves the ability to carry out number functions effectively, understand mathematical techniques such as estimation and approximation, and understand basic finance (Durrani & Tariq, 2012;Washer, 2007:62). Teamwork or collaborative skills improve communication among members (Archer & Davidson, 2008) and improve job performance (Love et al, 2002).…”
Section: Page34mentioning
confidence: 99%